Evaluation of Cuban oyster resource status (Crassostrea spp.) and reference points for its management - Betanzos-Vega, Abel; Alzugaray-Martínez, Romina; Puga-Millán, Rafael; Tripp-Quezada, Arturo; Mazón-Suástegui, José Manuel (Revista de Biología Marina y Oceanografía, 2023)
Oyster Crassostrea spp. is the bivalve mollusk with the largest commercial volume in Cuba. Populations should be assessed for their management and conservation, which has been performed but with different methodologies and only in certain localities, making it difficult to evaluate and compare between periods and regions. Therefore, current state of the resource was to be determined according to maximum sustainable yield (MSY), biomass for the maximum sustainable yield (BMSY), and corresponding fishing mortality rate (FMSY). Catch Maximum Sustainable Yield (CMSY) model was applied with Monte Carlo method, resource biomass and exploitation were evaluated for northwestern (NW), northeastern (NE), southeastern (SE), and southwestern (SW) regions of the insular platform, as well as for periods (1960-1991 and 1992-2020). From 1992-2020, a 50% reduction in oyster landings was recorded when compared with 1960-1991 period, which was reflected in population indicators according to estimated fishery reference points. Based on applied model and method, current oyster fishery management is perceived as unsustainable with stock depletion and overfishing in NW, NE, and SW regions. Cuban SE region shows a more favorable status. Oyster farming should increase to obtain higher production and broodstock biomass to decrease fishing effort on wild populations.